If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6(2x+5)=-3(9+4x)
We simplify the equation to the form, which is simple to understand
6(2x+5)=-3(9+4x)
Reorder the terms in parentheses
+(+12x+30)=-3*(9+4x)
Remove unnecessary parentheses
+12x+30=-3+*(+9+4x+)
Reorder the terms in parentheses
+12x+30=+(-27-12x)
Remove unnecessary parentheses
+12x+30=-27-12x
We move all terms containing x to the left and all other terms to the right.
+12x+12x=-27-30
We simplify left and right side of the equation.
+24x=-57
We divide both sides of the equation by 24 to get x.
x=-2.375
| 65.6t^2-143.1t+131.5=0 | | 2a^2-a-28= | | (9x-6)=(7x+7) | | 22+2y-6=9y-12-3y | | x^2-x-67=5 | | 7/(y^2-y-2)=1/(y-2)-2/(y+1) | | X+(1/x)=(13/6) | | 2x/2=100/2 | | -2(a-3b-6c)= | | 0.5(2b-3)-0.1=0.4(6+2b) | | 5x-9=6x-1 | | x+x-15+5=85+15 | | 3g=13g-140 | | -5y-8=12 | | 0.5-0.05= | | x=80000+0.2y | | 3/5(x+3)=1/6 | | 176-6x=21x+17 | | 0.05-0.5= | | -3(v+3)=-8v-29 | | 8x+9=x+5 | | 2(5x-3)=3-(5+2x) | | 12.50+1.50+1.50= | | 4/3(21) | | 4/3x21 | | 2[3d+7]=5+6d | | x-28=24 | | 8[g-3]=24 | | 2/9x45 | | (x-2)-(3/4) | | 40=2y+10 | | 3(2e+5)-3e=-15 |